Revision for prosthetic joint infection following hip arthroplasty: Evidence from the National Joint Registry. Issue 6 (June 2017) - Lenguerrand, E.; Whitehouse, M. R.; Beswick, A. D.; Jones, S. A.; Porter, M. L.; Blom*, A. W.
Abstract : Objectives: We used the National Joint Registry for England, Wales, Northern Ireland and the Isle of Man (NJR) to investigate the risk of revision due to prosthetic joint infection (PJI) for patients undergoing primary and revision hip arthroplasty, the changes in risk over time, and the overall burden created by PJI. Methods: We analysed revision total hip arthroplasties (THAs) performed due to a diagnosis of PJI and the linked index procedures recorded in the NJR between 2003 and 2014. The cohort analysed consisted of 623 253 index primary hip arthroplasties, 63 222 index revision hip arthroplasties and 7585 revision THAs performed due to a diagnosis of PJI. The prevalence, cumulative incidence functions and the burden of PJI (total procedures) were calculated. Overall linear trends were investigated with log-linear regression. Results: We demonstrated a prevalence of revision THA due to prosthetic joint infection of 0.4/100 procedures following primary and 1.6/100 procedures following revision hip arthroplasty. The prevalence of revision due to PJI in the three months following primary hip arthroplasty has risen 2.3-fold (95% confidence interval (CI) 1.3 to 4.1) between 2005 and 2013, and 3.0-fold (95% CI 1.1 to 8.5) following revision hip arthroplasty. Over 1000 procedures are performed annually as a consequence of hip PJI, an increase of 2.6-fold between 2005 and 2013. Conclusions: Although the risk of revision due to PJI following hip arthroplasty is low, it is rising and, coupled with the established and further predicted increased incidence of both primary and revision hip arthroplasty, this represents a growing and substantial treatment burden. Cite this article : E. Lenguerrand, M. R. Whitehouse, A. D. Beswick, S. A. Jones, M. L. Porter, A. W. Blom. Revision for prosthetic joint infection following hip arthroplasty: Evidence from the National Joint Registry. Bone Joint Res 2017;6:391–398. DOI: 10.1302/2046-3758.66.BJR-2017-0003.R1.